The Effect of the Low Glutamate Diet on the Reduction of Psychiatric Symptoms in Veterans With Gulf War Illness: A Pilot Randomized-Controlled Trial - Brandley, Elizabeth T.; Kirkland, Anna E.; Baron, Michael; Baraniuk, James N.; Holton, Kathleen F. (Frontiers in Psychiatry, 2022)
The objective of this study was to examine the effects of the low glutamate diet on anxiety, post-traumatic stress disorder (PTSD), and depression in veterans with Gulf War Illness (GWI). The low glutamate diet removes dietary excitotoxins and increases consumption of micronutrients which are protective against glutamatergic excitotoxicity. This study was registered at ClinicalTrials.gov (NCT#03342482). Forty veterans with GWI completed psychiatric questionnaires at baseline and after one-month following the low glutamate diet. Participants were then randomized into a double-blind, placebo-controlled crossover challenge with monosodium glutamate (MSG; a dietary excitotoxin) vs. placebo over three consecutive days per week, with assessments on day three. Data were analyzed across the full sample and with participants categorized by baseline symptom severity. Pre-post-dietary intervention change scores were analyzed with Wilcoxon signed-rank tests and paired sample t-tests across the full sample, and changes across symptom severity categories were analyzed using ANOVA. Crossover challenge results were analyzed with linear mixed modeling accounting for challenge material (MSG v. placebo), sequence (MSG/placebo v. placebo/MSG), period (challenge week 1 v. week 2), pre-diet baseline symptom severity category (minimal/mild, moderate, or severe), and the challenge material*symptom severity category interaction. A random effect of ID(sequence) was also included. All three measures showed significant improvement after one month on the diet, with significant differences between baseline severity categories. Individuals with severe psychological symptoms at baseline showed the most improvement after one month on the diet, while those with minimal/mild symptoms showed little to no change. Modeling results from the challenge period demonstrated a significant worsening of anxiety from MSG in only the most severe group, with no significant effects of MSG challenge on depression nor PTSD symptoms. These results suggest that the low glutamate diet may be an effective treatment for depression, anxiety, and PTSD, but that either a) glutamate is only a direct cause of symptoms in anxiety, or b) underlying nutrient intake may prevent negative psychiatric effects from glutamate exposure. Future, larger scale clinical trials are needed to confirm these findings and to further explore the potential influence of increased micronutrient intake on the improvements observed across anxiety, PTSD, and depression.